Non-specific peaks generated by animal DNA during human STR analysis: Peak characteristics and a novel analysis method for mixed human/animal samples. (November 2018) - Inokuchi, Shota; Mizuno, Natsuko; Nakanishi, Hiroaki; Saito, Kazuyuki; Kitayama, Tetsushi; Fujii, Koji; Nakahara, Hiroaki; Sekiguchi, Kazumasa
Graphical abstract: Highlights: DNA of animals at the crime scene is amplified by HID kit amelogenin primers. Non-specific peaks generated by animal DNA differ among animal families. Blocking PCR was developed for analysis of only animal DNA from mixed samples. This method could simultaneously perform HID and animal family discrimination. Abstract: Forensic human identification (HID) laboratories occasionally encounter non-specific peaks generated by non-human DNA. Casework samples for human short tandem repeat (STR) profiling may be contaminated by animal DNA because of the specific environment or situation from which they were obtained. Validation studies for HID kits have reported that non-specific peaks generated from some animals are observed near the human amelogenin peak. In this study, we first revealed that DNA sequences associated with the non-specific peaks generated from animal DNA differ from one animal family to the other. However, non-specific peaks cannot be analyzed using the remainder of polymerase chain reaction (PCR) products left over from conventional HID kits when human and animal DNA are mixed. To overcome this issue, we have developed a novel analysis method of using non-specific peaks generated from animal DNA in human STR profiling to identify the source of contaminating animal DNA at the family level. The method applied here is termed as blocking PCR, which involves selective animal DNA re-amplification by blocking nontarget human amelogenin DNA amplification using an oligonucleotide probe that specifically binds to human amelogenin using the remaining PCR product from the HID kit. Our data demonstrated that HID and family discrimination among animals that are often encountered in forensic contexts could be performed simultaneously. This study enabled recovery of more information from limited quantities of casework samples contaminated with animal DNA, which would be useful for forensic HID scientists.